KEPEMIMPINAN KEPALA SEKOLAH BERBASIS BUDAYA ETIS DALAM MENINGKATKAN MUTU SEKOLAH - -, Istiharoh; Muntaqo, Lutfan; Shidiq, Ngarifin (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2023)
This article aims to analyze the leadership of the principal based on ethical culture in improving school quality at MI Ma'arif Kaliwiro Wonosobo. This field research utilizes information obtained from research subjects through data collection instruments using a qualitative phenomenological approach with an inductive explanatory pattern. The research results show that the principal leads by building an ethical culture in the school, namely religious ethics, honesty, justice, assertiveness, discipline and caring. Based on this ethical culture, the principal communicates the organization to all its members. In improving school quality, the principal has strategies as the basis for an ethical culture, namely: 1) establishing religious ethical standards as a culture for educators and students; 2) acting as a model or example for subordinates; 3) paying attention to aspects of heterogeneity in developing an ethical culture in the school, 4) thinking about long-term consequences, 5) fighting for the fate of subordinates. This ethical culture has an impact on improving school quality from academic and behavioral aspects. Academically, students are able to understand the material presented by educators. Behaviorally, it makes students more diligent in worship, and educators and staff better understand their role in guiding students.